(untitled) (Indian Journal of Animal Production and Management, 2017)
A field study was conducted to know the existing breeding, feeding and housing management practices followed by the landless, small farmer and commercial milk producers in Guntur district of Andhra Pradesh. Commercial milk producers reared both Murrah and Graded Murrah buffaloes, whereas small farmers and landless milk producers maintain mostly Graded Murrah buffaloes. Green fodder production was higher in commercial (100%) and small farmers (97%) than in landless milk producers (13%). Supplementation of mineral mixture was found to be higher in commercial milk producers (90%) than that in small farmers (35%) and landless milk producers (16%). All most all landless (99%) category housed their buffaloes in the open area but only the commercial milk producers were maintaining the sheds (50%) and protect the animals from adverse climatic conditions. Majority of commercial (86%) and small farmers (27%) arranged cooling devices like fans in the buffalo sheds.